Influence of age, mode of delivery and parity on the prevalence of posterior pelvic floor dysfunctions - Murad-Regadas,Sthela Maria (2011)
CONTEXT: The correlation between vaginal delivery, age and pelvic floor dysfunctions involving obstructed defecation is still a matter of controversy. OBJECTIVES: To determine the influence of age, mode of delivery and parity on the prevalence of posterior pelvic floor dysfunctions in women with obstructed defecation syndrome. METHODS: Four hundred sixty-nine females with obstructed defecation syndrome were retrospectively evaluated using dynamic 3D ultrasonography to quantify posterior pelvic floor dysfunctions (rectocele grade II or III, rectal intussusception, paradoxical contraction/non-relaxation of the puborectalis and entero/ sigmoidocele grade III). In addition, sphincter damage was evaluated. Patients were grouped according to age (<50y x >50y) and stratified by mode of delivery and parity: group I (<50y): 218 patients, 75 nulliparous, 64 vaginal delivery and 79 only cesarean section and group II (>50y): 251 patients, 60 nulliparous, 148 vaginal delivery and 43 only caesarean section. Additionally, patients were stratified by number of vaginal deliveries: 0 - nulliparous (n = 135), 1 - vaginal (n = 46), >1 - vaginal (n = 166). RESULTS: Rectocele grade II or III, intussusception, rectocele + intussusception and sphincter damage were more prevalent in Group II (P = 0.0432; P = 0.0028; P = 0.0178; P = 0.0001). The stratified groups (nulliparous, vaginal delivery and cesarean) did not differ significantly with regard to rectocele, intussusception or anismus in each age group. Entero/sigmoidocele was more prevalent in the vaginal group <50y and in the nulliparous and vaginal groups >50y. No correlation was found between rectocele and the number of vaginal deliveries. CONCLUSION: Higher age (>50 years) was shown to influence the prevalence of significant rectocele, intussusception and sphincter damage in women. However, delivery mode and parity were not correlated with the prevalence of rectocele, intussusception and anismus in women with obstructed defecation.